Učinki telesne dejavnosti na zdrav življenjski slog - Arčon, Matevž (Šport (Ljubljana), 2023)
In the short term, physical activity plays a key role in human health by acutely regulating metabolism and appetite. In the longer term, however, physical activity can also elicit benign physiological adaptations such as improved cardiovascular health and skeletal muscle mass, depending mainly on the exercise modality. Endurance exercise can increase cardiorespiratory capacity, whereas resistance exercise can augment skeletal muscle mass and muscle strength. And although these are preferable exercise modalities for optimal health, adherence on a populational level is still difficult to ensure. Walking is the most widely adopted form of physical exercise and can be a viable exercise strategy in weight management and sarcopenia. Nevertheless, even this form of physical exercise is subject to age-related and weight loss-related reductions which are represented in daily steps and the energy expenditure they yield. In this review, we aim to elucidate the effects of weight loss and biological aging on physical activ- ity and physical activity energy expenditure. In addition, we present general guidelines for physical activity that can contribute to healthy aging and succesful weight managment.
Keywords: staranje; šport; športna rekreacija; telesna aktivnost; telesna masa